Movers and shakers: Leadership attributes for a successful lean manufacturing implementation - Norhana, Mohd Aripin; Suhaidah, Hussain; Gusman, Nawanir (GBMR, 2023)
Purpose: This study aims to investigate the leadership attributes for successful lean manufacturing implementation. Design/methodology/approach: This study employed a case study in European automotive manufacturing plants through a series of interviews with six informants from four countries. The six informants represent each subgroup from the job responsibilities. Findings: The result comprises four main lean leadership attributes for successful lean manufacturing implementation. First, management commitment, involvement, and engagement, followed by management mission and vision. In addition, management coaching and effective communication were highlighted as important attributes of lean leaders. Research limitations/implications: Further studies could extend this study using a mixedmethod approach. Applying both methods will contribute significantly to providing a holistic view, providing a breadth and depth to understanding phenomena that neither qualitative nor quantitative research approaches alone could support. Practical implications: This study contributes to expanding the boundary of the existing literature and contributes to the body of knowledge while providing insights to practitioners in tailoring strategies to strategize the roadmap, ensuring the implementation is ongoing by integrating the leadership role to reap the maximum benefit of lean implementation. Originality/value: Although several studies presented positive relationships of leaders and the characteristics, skills, and behaviors of leaders that facilitate lean success from a case study, this study examines the leadership attributes from various contexts to facilitate a deeper comparative analysis.